Modelling and Optimizing the Removal of Methylene Blue by a Mixture of Titaniferous Sand and Attapulgite Using Complete Factorial Design - Ba, Kalidou; Toure, Alpha Ousmane; Diop, El Hadji Moussa; Sambe, Falilou Mbacke; Diop, Codou Guéye Mar (European Scientific Journal, ESJ, 2021)
This paper focuses on the removal of methylene blue by adsorption using a mixture of titaniferous sand and attapulgite. The different adsorbents were characterized by X-ray fluorescence spectroscopy and their different parameters such as pH, zero charge potential, and specific surface area were determined. The experiments performed were optimized and modeled by a full 2-level and 4-factor design. The four factors are the ratio of titaniferous sand and attapulgite, the concentration of methylene blue, pH, and time. These vary from 4 to 19, 20 to 100 mg/L, 2 to 9, and 30 to 150 min respectively. The study of the effects of the different factors showed that the effect of methylene blue concentration and pH significantly influence the adsorption capacity and removal efficiency of the dye. The optimum parameters (adsorbent ratio, adsorbate concentration, pH and time) obtained for the adsorption capacity through the desirability function are: 19, 100mg/L, 9 and 150min. Those obtained for the yield are: 4, 100mg/L, 9, 150min. The pseudo second order adsorption kinetics gave an equilibrium adsorption capacity qe (calculated) = 7.6863 mg/g which is almost equal to that obtained experimentally qe (exp) = 7.3562 mg/g. This shows that the pseudo second order kinetic model is the adequate mathematical model to describe the methylene blue adsorption phenomenon on the mixture of titaniferous sand and attapulgite. The thermodynamic study showed that the methylene blue adsorption reaction is exothermic, non-spontaneous, and the degree of disorder of the particles at the adsorbing surface decreases.